2014
DOI: 10.1016/j.joi.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Journal topic citation potential and between-field comparisons: The topic normalized impact factor

Abstract: The journal impact factor is not comparable among fields of science and social science because of systematic differences in publication and citation behaviour across disciplines. In this work, a source normalization of the journal impact factor is proposed. We use the aggregate impact factor of the citing journals as a measure of the citation potential in the journal topic, and we employ this citation potential in the normalization of the journal impact factor to make it comparable between scientific fields. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The idea of comparing publications with other similar publications selected based on shared references (i.e., bibliographic coupling) is also discussed by Braun (1993, 1996). A somewhat similar idea at the level of journals instead of individual publications is proposed by Dorta-González et al (2014).…”
Section: Normalized Indicators Based On Highly Cited Publicationsmentioning
confidence: 87%
“…The idea of comparing publications with other similar publications selected based on shared references (i.e., bibliographic coupling) is also discussed by Braun (1993, 1996). A somewhat similar idea at the level of journals instead of individual publications is proposed by Dorta-González et al (2014).…”
Section: Normalized Indicators Based On Highly Cited Publicationsmentioning
confidence: 87%
“…A further longitudinal study needs to be conducted to verify the direct impact of database enlistment. Second, this study targeted the biomedical and health science journals published in Korea as a whole, but the distribution of journal characteristics and citation behaviors might be different in sub-areas of biomedical sciences [ 23 ]. Therefore, research in this area may be expanded by considering the specialty categories of biomedical and health sciences.…”
Section: Discussionmentioning
confidence: 99%
“…However, in bibliometric studies, there is no uniform recommendation regarding study design of these types of bibliometric studies. For example, it has been reported that in the biomedical field, list of fifty or more citations is common, while in mathematics less than twenty citations are most common [76].…”
Section: Limitationsmentioning
confidence: 99%